Teen Athlete with Recurrent Rhabdomyolysis: A Case Report (Global Journal of Medical Research, 2021)
Background Rhabdomyolysis is a frequent disorder in the pediatric emergency room and it can result from various acquired and inherited causes Case presentation We report the case of a 15-year-old female triathlon athlete with recurrent exertional rhabdomyolysis The clinical severity alerted for a subjacent cause and further investigation was taken leading to the diagnosis of very long-chain acyl-CoA dehydrogenase VLCAD deficiency Conclusion Exertional rhabdomyolysis may be the first manifestation of a metabolic myopathy like VLCAD deficiency VLCAD deficiency has a broad clinical spectrum and the most common is the late-onset which presents mainly with episodic symptoms with predominant muscular involvement and exercise-induced rhabdomyolysis
Keywords: adolescent medicine; exertional rhabdomyolysis; sports medicine; metabolic myopathy; VLCAD deficiency